Game-Based Learning in Requirements Engineering: An Overview - Soo M.T.; Aris H. (Institute of Electrical and Electronics Engineers Inc., 2023)
E-learning; Engineering education; Requirements engineering; Software engineering; Software testing; Students; Active Learning; Educational game; Game-based Learning; Gamification; Keyword searching; Learning objectives; Subject matters; Teaching and learning; Serious games